Domestic violence against women in Campo Grande, Mato Grosso do Sul: situation and reality (Research, Society and Development, 2021)
Objective: to analyze the situation of domestic violence against women in Campo Grande/Mato Grosso do Sul. Methodology: This is a quantitative and transversal research. This research contains data provided by the State Department of Justice and Public Security of Mato Grosso do Sul regarding cases reported in police reports, filled out at the First Police Station for Specialized Assistance to Women, from January 2010 to December 2014. The collection The data collection took place from April to August 2015. Results: This study showed that of the 11,084 reported cases of bodily injury 59.8% were registered within the family. In relation to rapes and homicides that occurred in the family context, there was a higher incidence of cases in brown women and over 25 years old. The most violent neighborhoods in the capital of Mato Grosso do Sul are the most distant and with the most units of social support network and health treatment. Conclusion: the spatial distribution of cases of domestic violence against women and support units to fight violence allowed to verify the predominance of violence in urban regions with high population density and low income, showing a relationship between violence and socioeconomic issues.